Metalloproteinase-2 in failed back surgery syndrome caused by epidural fibrosis: can it play a role in persistent pain? - Bielewicz, Joanna; Daniluk, Beata; Kamieniak, Piotr (Frontiers in Human Neuroscience, 2023)
Purpose Failed Back Surgery Syndrome (FBSS) occurs in 10–40% of patients treated surgically due to disk herniation (DH). There are several factors that can cause a predisposition to FBSS, but the exact pathomechanism has not been elucidated. The aim of this study was to investigate Metalloproteinase-2 (MMP-2) and Tissue Inhibitor of Metalloproteinase-2 (TIMP-2) activities in a homogeneous group of FBSS patients with epidural fibrosis in comparison to its activity in patients with surgically treated DH. Methods DH, FBSS, and control (CG) groups consisted of 30 subjects. The patients were assessed clinically by the Numerical Rating Scale (NRS), McGill Pain Questionnaire (SF -MPQ), Oswestry Disability Index (ODI), and Beck Depression Inventory (BDI). Serum concentrations of MMP-2 and TIMP-2 were measured by using the immunoenzymatic method. Results There was a significantly higher MMP-2 expression (medians: 4797.49 vs. 2656.65; p < 0.0001) and TIMP-2 concentration (medians: 166.40 vs. 109.60; p < 0.0001) in the DH compared to the CG. Significantly higher MMP-2 expression (4219.95 vs. 2656.65; p < 0.0001) and TIMP-2 concentration (medians: 150.17 vs. 109.60; p = 0.0003) were also found in the FBSS compared to the CG. The activity of MMP-2, measured as MMP-2/TIMP-2, did not significantly change between the DH, FBSS, and CG. MMP2 expression (p < 0.0001) and TIMP-2 concentration (p < 0.0001) were significantly higher in the DH than FBSS. Conclusion Results indicate the presence of a contribution of MMP-2 and TIMP-2 in DH and FBSS. Unchanged activity of MMP-2 can indicate an insufficiency in the MMP-2 repair system in both diseases. Lower MMP-2 expression and TIMP-2 concentration in the FBSS group can reflect the chronicity of the process.